2010
DOI: 10.1016/j.ijid.2010.03.013
|View full text |Cite
|
Sign up to set email alerts
|

The effect of Helicobacter pylori infection on growth velocity in young children from poor urban communities in Ecuador

Abstract: These results suggest that linear growth velocity is reduced in young children during the initial phase of Helicobacter infection.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
26
1
2

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(29 citation statements)
references
References 26 publications
0
26
1
2
Order By: Relevance
“…The above studies (17,27) demonstrated slower growth among young toddlers, following newly acquired H pylori infection; the effect of that may be greater than that of infection in the chronic phase. In a study of healthy Arab children in Israel of preschool (3-5 years) and school age (6-9 years), we found that the adjusted mean HAZ score at follow-up was significantly lower among H pylori-infected children than among uninfected ones: 0.15 (95% CI 0.02-0.29) and 0.45 (95% CI 0.29-0.60), respectively (Pv ¼ 0.002) (29).…”
Section: Evidence From Longitudinal Studiesmentioning
confidence: 93%
“…The above studies (17,27) demonstrated slower growth among young toddlers, following newly acquired H pylori infection; the effect of that may be greater than that of infection in the chronic phase. In a study of healthy Arab children in Israel of preschool (3-5 years) and school age (6-9 years), we found that the adjusted mean HAZ score at follow-up was significantly lower among H pylori-infected children than among uninfected ones: 0.15 (95% CI 0.02-0.29) and 0.45 (95% CI 0.29-0.60), respectively (Pv ¼ 0.002) (29).…”
Section: Evidence From Longitudinal Studiesmentioning
confidence: 93%
“…Helicobacter pylori ( H. pylori ) is a common bacterial infection associated with gastrointestinal and extra‐gastrointestinal diseases. Commonly acquired in childhood, the organism is transmitted via person‐to‐person contact and through consumption of contaminated water . Infections are more common in developing countries with reported prevalence of as high as 90% .…”
mentioning
confidence: 99%
“…Helicobacter pylori infections have been acknowledged to contribute to the majority of gastric carcinoma cases worldwide . Growth retardation and nutritional deficiencies particularly iron deficiency anemia, resulting from impaired gut iron absorption in children, have also been associated with H. pylori infections in developing countries …”
mentioning
confidence: 99%
“…Duodenal ulcers can appear in adolescence and in late childhood, but gastric ulcer is uncommon and gastric cancer is also very rare among children . Several studies addressed the association between H. pylori infection and growth during childhood . Some studies showed negative influence of H. pylori on nutritional status of children with both height and weight being affected , or only height being affected .…”
mentioning
confidence: 99%
“…Several studies addressed the association between H. pylori infection and growth during childhood [4][5][6][7][8][9][10]. Some studies showed negative influence of H. pylori on nutritional status of children with both height and weight being affected [6,8,10], or only height being affected [7,9]. Other reports, however, suggested no adverse impact of H. pylori infection on growth [11][12][13].…”
mentioning
confidence: 99%